View of mathematics – an investigation of Estonian university students - Kaldo, Indrek (NOMAD Nordic Studies in Mathematics Education, 2014)
This study reports on first-year Estonian university students’ view of mathematics. The data was collected from 970 university students of different disciplines. The participants filled out a Likert-type questionnaire that was developed using previously published instruments. This paper documents and analyses the data from the study. In this study students agreed that mathematics is an important and valuable subject. Female students have a more positive view of mathematics than male students. Science students have a more positive view of mathematics than non-science students.